Effect of a short training in communication abilities with the CICAA method in an university in Lima, Peru - Ticse Aguirre, Ray Willy (2019)
Objective: To evaluate the efficacy of a short training in communication abilities with the CICAA method in a university in Lina, Peru. Methods: A before-after study design was undertaken where each resident was a control. Participants: 25 first year residents of family medicine, internal medicine and pediatrics of Universidad Peruana Cayetano Heredia. Intervention: training in the CICAA method which includes four areas grouped in three domains; connecting (domain 1), identifying and learning (domain 2); and remembering and helping (domain 3). A short training of 26 hours was conducted including lectures, workshops, and play-role activities for students and teachers. A structure objective assessment with the participation of two standardized patients was carried-out. CICAA score was used to evaluate the clinical interview one week before and after the training. Results: The mean value of the overall evaluation was 29.84 ± 1.44; 8.72 ± 0.33, 12.8 ± 1.02 and 8.32 ± 0.67 for domains 1-3, respectively. Values after the training were 40.84 ± 1.32; 11 ± 0.26, 16.04 ± 1.01 and 13.44 ± 0.51, for domains 1-3, respectively. Conclusion: The implementation of a short training in communication abilities based on lectures and play-role has a positive impact on an early evaluation.